2020
DOI: 10.1159/000506053
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Kidney Stone Disease in Chinese Patients with Type 2 Diabetes Mellitus

Abstract: Objectives: To investigate the characteristics of kidney stone disease (KSD) among the Chinese population with type 2 diabetes mellitus (T2DM) and identify sex-specific factors associated with KSD. Methods: A single-center, cross-sectional analysis was performed among Chinese patients with T2DM. KSD was identified by ultrasonography or computed tomography results. Demographic data, physical measurements, laboratory measurements, comorbidities, and related medication data were collected and analyzed. Binary log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It has been hypothesised that sex hormones may have a significant role in gender differences for KSD, and 5 studies were identified which investigated this further [22][23][24]26]. Peerapen et al investigated the effects of oestrogen in the kidney [22].…”
Section: Role Of Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesised that sex hormones may have a significant role in gender differences for KSD, and 5 studies were identified which investigated this further [22][23][24]26]. Peerapen et al investigated the effects of oestrogen in the kidney [22].…”
Section: Role Of Hormonesmentioning
confidence: 99%
“…There is some evidence to support a protective role of ACE-inhibitors on stone formation [25]. Xiao et al performed a cross-sectional analysis in order to investigate this further amongst a population with type 2 diabetes mellitus (DM) [26]. The protection achieved among women was superior to men.…”
Section: Role Of Hormonesmentioning
confidence: 99%
“…A retrospective study conducted between 2014 and 2018 in China reported the overall prevalence of kidney stones among diabetic men and women (17 and 12.6%, respectively), which was twice as high as the general population. Additionally, they reported an annual rise in stone prevalence, which was more notable among diabetic male stone formers [30]. Moreover, using the NHANES from 2013 to 2016, Elia et al [35] reported a significantly higher prevalence of kidney stones among patients with disabilities than patients without disabilities (16.1 vs. 9.2%), and that around one-third of stone formers in the United States were patients with disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the findings of the studies that met our inclusion criteria. Twenty-three studies were identified reporting on urolithiasis epidemiology, prevalence, and trends from 11 different countries in the past 2 years [6 ▪▪ ,12,13 ▪ ,14 ▪ ,15,16 ▪▪ ,17,18 ▪ ,19–26,27 ▪ ,28–33].…”
Section: Resultsmentioning
confidence: 99%
“…Persistent over-acidification plays a decisive role in this regard. Epidemiologic studies have shown that metabolic syndrome is strongly associated with UAS due to various metabolic and environmental factors promoting insulin resistance and stone formation within urine samples (Abou-Elela 2017 ; Bamberger et al 2021 ; Xiao et al 2020 ). Stone patients who are obese or diabetic tend to have higher proportions of total stones consisting of UAS compared to those who possess normal body mass indices (BMI) or serum glucose levels (Daudon et al 2006a , 2006b ).…”
Section: Introductionmentioning
confidence: 99%